The Effect of the pH of Aquades Solvent on the Physicochemical Characteristics of Parijoto (Medinilla Speciosa) Extract - Effendi, Nazmirafa; Septiana, Aisyah Tri; Handayani, Isti (Indonesian Journal of Food Technology, 2024)
Parijoto is an endemic Indonesian plant that is believed to have many health benefits. Parijoto fruit extraction is an effort to obtain extracts so that they are more applicable in the food sector. This research aims to examine the effect of the pH of the distilled water solvent on the characteristics of parijoto extract. Extraction was carried out using the Microwave-Assisted Extraction (MAE) method. Aquades was chosen as a solvent because it is safe, easy to obtain, and cheap. pH adjustment was carried out using citric acid and Ca(OH)2 to produce pH 2,4,6,9 and 11. As a control, distilled water was not adjusted for pH. The research was conducted experimentally using a Randomized Block Design. Repetition was carried out 5 times. The resulting extract was observed for levels of anthocyanins, vitamin C, total titratable acids, pH, and total dissolved solids. Based on the results, the highest levels of anthocyanins (31.64 mg/L), total titratable acids (10.36%), and total dissolved solids (3.63 oBrix), were produced using distilled water pH 2, but vitamin C (26.64 mg/100 g), and the pH of the extract (1.92) was the lowest. The highest levels of vitamin C (77.40 mg/100 g) were produced in distilled water without pH adjustment (pH 6.0).